FORMULASI MASKER GEL DENGAN EKSTRAK DAUN MANGGA ARUMANIS (Mangifera Indica L.) SEBAGAI BAHAN AKTIF - Tasyah Helgiera; Astriani Natalia Br Ginting; Roy Indrianto Bangar (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2026)
Exposure to ultraviolet (UV) radiation and environmental pollution can generate free radicals that contribute to skin damage and accelerate premature aging. One approach to protect the skin from these effects is the use of antioxidants derived from natural sources. Arumanis mango leaves (Mangifera indica L.) contain secondary metabolites such as flavonoids, tannins, and saponins which have potential antioxidant activity and can be utilized as active ingredients in cosmetic formulations. This study aimed to formulate a gel mask containing ethanol extract of arumanis mango leaves and to evaluate the physical quality of the preparation. The extract was obtained using the maceration method with 96% ethanol as the solvent. The gel mask was formulated into three different extract concentrations, namely 0%, 4%, and 6%. The physical evaluation included organoleptic test, homogeneity, pH, spreadability, and drying time tests. The results showed that the gel mask preparations exhibited good physical characteristics, with homogeneous appearance, pH values ranging from 5.16–6.26, spreadability of 5.5–6.8 cm, and drying time of 17–20 minutes. The variation in extract concentration affected the color of the preparation but did not significantly influence the overall physical stability of the gel. Therefore, ethanol extract of arumanis mango leaves can be formulated into a gel mask preparation that meets the physical quality requirements for skincare products.